PENGARUH KOMPETENSI, PENGEMBANGAN KARIR DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BPR ULATIDANA RAHAYU KABUPATEN GIANYAR - I Nyoman Agus Hendra Maryawan; Ni Made Dwi Puspitawati; Ni Luh Gede Putu Purnawati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
Human resources are a very important element in every company. In essence, a company must pay attention to the quality of human resources because human resources are the main key in realizing the company's goals. In this regard, good quality human resources are one of the factors that affect the quality of employee performance so that the success of a company can be measured in general, it cannot be separated from the ability of human resources to maximize the achievement of goals and targets set by the company. The best management of human resources will improve the quality of human resources because the quality of human resources is a strength for the company to achieve targets and goals, one of which is by improving employee performance. This study aims to test whether there is an influence of competence, career development and work discipline on employee performance at PT. BPR Ulatidana Rahayu, Gianyar Regency. The population of this study were employees at PT. BPR Ulatidana Rahayu, Gianyar Regency. The determination of respondents was selected using a non-probability sampling technique that does not provide equal opportunities or opportunities for each element or member of the population to be selected as a sample with a saturated sampling method and a sample size of 35 people. The data collection technique used a questionnaire distribution method. Data analysis techniques using multiple linear analysis techniques and data analysis assisted by the SPSS 26 computer program. The results of the study showed that competency has a significant positive effect on employee performance at PT. BPR Ulatidana Rahayu, Gianyar Regency, career development has a significant positive effect on employee performance at PT. BPR Ulatidana Rahayu, Gianyar Regency and work discipline has a significant positive effect on employee performance at PT. BPR Ulatidana Rahayu, Gianyar Regency.